Creative Encounter Festschrift for Herman Salinger - Phelps, Leland R.; Tilo Alt, A. (UNC Studies in the Germanic Languages and Literatures, 1978)
A collection of thirteen essays by comparatists and Germanists published in celebration of the scholar and poet Herman Salinger. The essays range from Greek antiquity to the twentieth century-from the Sophoclean "Electra" to Rilke. Two poems by Rudolf Hagelstange and Karl Krolow, Tabula Gratulatoria, and a bibliography of Herman Salinger's publications are also included in the volume. The contributors include: John Kunstmann, Helmut Rehder, Leland Phelps, Frank Borchardt, Eugene Falk. Haskell Block, Beda Allemann, James O'Flaherty, Tilo Alt, William Rey, George Schoolfield, and Hermann Weigand.